Allium sulaimanicum: A new Allium species and section from Pakistan - Khan, Nazar; Friesen, Nikolai; Sultan, Amir; Fritsch, Reinhard M.; Khan, Tahir; Ishaq, Kamran (Frontiers in Plant Science, 2022)
A new species, Allium sulaimanicum, is described from northern Balochistan and southern Khyber Pakhtunkhwa in Pakistan based on morphological, molecular, and cytological studies. The new species is characterised by long runner-like cylindrical rhizomes of adult plants, cylindrical bulbs, linear leaves with minute soft hairs along veins, campanulate perigonium, and white to creamy white, ovate to elliptical, 4.5–5-mm-long acute tepals, with brownish to purplish nerves, stamens as long as to slightly longer than tepals, yellow to brick red anthers, hexagonal ovary, and white and papillate/warty along angles. The presence of long herbaceous rhizomes indicated serious isolation of the new species; hence, a new section Sulaimanicum is proposed to accommodate the new species. The new species is diploid with a chromosome number of 2n = 16. Detailed morphological description, illustrations, phylogenetic analyses based on sequences of plastid spacers (rpl32-trnL (UAG) and trnQ-rps16) and nuclear ITS, karyotype features, and a distribution map of the new species are provided.